Nutritional management of chronic kidney disease in dogs: Literature review (Research, Society and Development, 2023)
Chronic kidney disease is characterized by persistent alterations in kidney function and structure for more than three months. It is a condition frequently diagnosed in the routine of the veterinarian in dogs and cats, even in young individuals, but mainly in the elderly due to the increased life expectancy of these domestic animals. CKD stands out as a disease with high morbidity and mortality for its carrier. As it involves irreversible damage to the nephrons, its treatment is palliative and directly linked to the improved quality and life expectancy of these patients, making early diagnosis extremely important for greater treatment effectiveness. Adequate nutritional management of the chronic renal patient is of utmost importance for a better clinical response of the patient, directly influencing their well-being and quality of life. Therefore, this study aims to conduct an updated literature review on the nutritional management of chronic kidney disease in dogs, which can be used as a research source by veterinary medicine students and veterinarians for better disease treatment and consequent improvement in the quality and life expectancy of these patients.